2020
DOI: 10.1371/journal.pone.0233075
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of limbal explant sites: Optimization of stem cell outgrowth in in vitro culture

Abstract: Simple limbal epithelial transplantation (SLET) and cultivated limbal epithelial transplantation (CLET) are proven techniques for treating limbal stem cell deficiency (LSCD). However, the precise regions that are most suitable for preparing explants for transplantation have not been identified conclusively. Accordingly, this in vitro study aimed at determining ideal sites to be selected for tissue harvest for limbal stem cell culture and transplantation. We evaluated cell outgrowth potential and the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Heterozygous mutation in the TP63 gene is also responsible for LESCs failure and results in drastic degeneration of corneal epithelial tissues [ 96 ]. ΔNp63α is the predominantly expressed isoform in LESC and in limbal basal cells [ 97 99 ], but not in cells that cover the central corneal surface [ 96 ] (Fig. 3C ).…”
Section: Role Of P63 In Epithelial Stem Cell Biologymentioning
confidence: 99%
“…Heterozygous mutation in the TP63 gene is also responsible for LESCs failure and results in drastic degeneration of corneal epithelial tissues [ 96 ]. ΔNp63α is the predominantly expressed isoform in LESC and in limbal basal cells [ 97 99 ], but not in cells that cover the central corneal surface [ 96 ] (Fig. 3C ).…”
Section: Role Of P63 In Epithelial Stem Cell Biologymentioning
confidence: 99%
“…Moreover, a murine study showed that a small population of LSCs regulated the immune reaction by inhibiting lymphocyte proliferation and altering cytokine production and highly expressed genes for various anti-apoptotic proteins 26 . This explanation might apply especially to patients with partial LSCD when the donor graft helps support the patient's remaining stem cell to repopulate the corneal epithelium, which gradually grows and eventually replaces the decaying donor cells, and maintain a normal ocular surface 27 .…”
Section: Slet Vs Cletmentioning
confidence: 99%
“…The study of Ekpo et al was based on five human cadaveric donor corneoscleral tissues. The culture details were described by Prabhasawat et al [30,31]. After preparation, the explant culture was washed in phosphate-buffered saline (PBS), incubated in dispase for 20 minutes at 37°C, washed in PBS again and then placed on a culture plate.…”
Section: Donor Tissue Location In the Limbusmentioning
confidence: 99%